Hubungan Layanan Bimbingan Kelompok Teknik Asertive Training dengan Kepercayaan Diri - Nasia, Nadia Patoluna Dalimunthe; Dewi, Ika Sandra (Prodi Bimbingan dan Konseling Islam, 2023)
The purpose of this study is to determine if there is a connection between the self-confidence of class X students at SMK Negeri 1 Perbaungan and the assertive training technique group guidance services. This examination test was taken utilizing a purposive inspecting procedure in light of foreordained rules. The information assortment procedure for this exploration is as a poll given to understudies with four sorts of scores gave, to be specific unequivocally concur, concur, dissent, emphatically conflict. This exploratory setup utilizes clear quantitative and correlational strategies. In view of the consequences of examination at SMK Negeri 1 Perbaungan, it shows that there is a connection between decisive preparation method bunch direction administrations and the self-assurance of class X understudies at SMK Negeri 1 Perbaungan. This is demonstrated by working out the Item Second connection test between factor X (Emphatic Preparation Specialized Gathering Direction Administrations) and variable Y (Self-assurance). Furthermore, seen from rcount = 0.261 with n = 67 at an importance level of 5%, the worth of rtable = 0.237 can be gotten. rcount > rtable, in particular (0.261 > 0.237).